Solomon Islands Tourism Investor Guide : A guide to investing in land for tourism development - International Finance Corporation (Washington, DC, 2022)
This Guide is designed to provide information that may be of help to potential tourism investors in navigating the process of investing in land for the purpose of tourism development in Solomon Islands.